2016
DOI: 10.1007/s13105-016-0497-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between irbesartan, peroxisome proliferator-activated receptor (PPAR-γ), and adiponectin in the regulation of blood pressure and renal function in spontaneously hypertensive rats

Abstract: Adiponectin exerts vasodilatory effects. Irbesartan, an angiotensin receptor blocker, possesses partial peroxisome proliferator-activated receptor gamma (PPAR-γ) agonist activity and increases circulating adiponectin. This study explored the effect of irbesartan alone and in combination with adiponectin on blood pressure, renal hemodynamic excretory function, and vasoactive responses to angiotensin II and adrenergic agonists in spontaneously hypertensive rat (SHR). Irbesartan was given orally (30 mg/kg/day) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
7
6
0
Order By: Relevance
“…Firstly, the natriuresis produced by adiponectin caused an increase in sodium and water excretion and could be contributory factor in reducing B.P. Secondly, adiponectin may inhibit Na+-K+-ATPase activity in renal proximal tubule cells of SHR diabetic rats, which supports our hypothesis that these drugs particularly adiponectin prevent the ANG II actions at various points along signaling pathway and in parallel with our previous findings (25).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Firstly, the natriuresis produced by adiponectin caused an increase in sodium and water excretion and could be contributory factor in reducing B.P. Secondly, adiponectin may inhibit Na+-K+-ATPase activity in renal proximal tubule cells of SHR diabetic rats, which supports our hypothesis that these drugs particularly adiponectin prevent the ANG II actions at various points along signaling pathway and in parallel with our previous findings (25).…”
Section: Discussionsupporting
confidence: 90%
“…We observed numerous significant findings in this experiment. Primarily, urinary excretion and plasma adiponectin concentrations were low in the diabetic SHRs, whereas, restored partially to those found in the WKY rats after pioglitazone administration which supports the previous findings, that through activation of PPAR-γ, adiponectin, prevents activation of the adrenoceptors and AT1 receptor (25). We administered adiponectin at a rate sufficient to increase its plasma concentration and urinary excretion as compared to normotensive rats.…”
Section: Discussionsupporting
confidence: 88%
“…Effect of exogenous pioglitazone, adiponectin, and a combination of pioglitazone and adiponectin on creatinine clearance (Cr.Cl), urinary creatinine (mg/ dl), urinary sodium concentration (urinary Na), absolute urinary sodium excretion (U Na V) fractional sodium excretion(FENa), urinary potassium (urinary K) and urinary sodium to potassium ratio (Na:K) in diabetic Spontaneously hypertensive rats. PLOS ONE adiponectin concentrations were low in the diabetic SHRs, whereas, restored partially to those found in the WKY rats after pioglitazone administration which supports the previous findings, that through activation of PPAR-γ, adiponectin, prevents activation of the adrenoceptors and AT1 receptor [25]. We administered adiponectin at a rate sufficient to increase its plasma concentration and urinary excretion as compared to normotensive rats.…”
Section: Discussionsupporting
confidence: 87%
“…The signi cance of NO in the kidney vasculature cannot be ruled out which performs various pivotal role including renal hemodynamics regulation, modulation of renal sympathetic neural activity and inhibition of tubular sodium reabsorptive mechanism (48). We observed that irbesartan @ (30 mg/kg/day) caused maximal dose for blockade of RAAS whilst its partial PPAR-γ agonistic activity also contributed in its B.P reduction and renoprotective characteristics in nondiabetic SHRs as observed previously in our ndings (49).…”
Section: Discussionsupporting
confidence: 72%